Fatigue crack growth lessons from thirty-five years of the Royal Australian Air Force F/A-18 A/B Hornet Aircraft Structural Integrity Program. (April 2020) - Main, B.; Molent, L.; Singh, R.; Barter, S.
Highlights: Fatigue crack growth lessons from a modern combat aircraft. Importance of quantitative fractography, fatigue test and short crack regime. Types of fatigue cracks and their growth in real aerospace structures. Aircraft Structural Integrity Program. Abstract: As the Royal Australian Air Force (RAAF) retires its fleet of F/A-18 A and B model Hornets, it is opportune to reflect upon some of the in-service fatigue crack growth lessons accrued from 35 years of the aircrafts Aircraft Structural Integrity Program (ASIP). In this paper, the authors have selected a small number of the key lessons and observations arising from real-world fatigue problems in the RAAF Hornet fleet that have contributed to advances in the state of the art of fatigue crack growth measurement and prediction. The importance of the lead crack concept, quantitative fractography, fatigue testing, nucleating discontinuities, the physically short crack regime, as well as individual aircraft tracking are given prominence. It is hoped that this review of the metal fatigue challenges for a highly stressed lightweight structure that have driven research into fatigue crack growth will be valuable to those aspiring to make impactful contributions to the field and the sustainment of aircraft fleets worldwide.